PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT DAN CUSTOMER EXPERIENCE TERHADAP CUSTOMER SATISFACTION MATAHARI KOTA BENGKULU - Fadilatunnisa, Fadilatunnisa; Bustami, Taufik (UM. Bengkulu, 2026)
This study aims to determine the Influence of Customer Relationship Management and Customer Experience on Customer Satisfaction of Matahari Kota Bengkulu consumers. This type of research is a type of quantitative descriptive research, the population of this study is Matahari Kota Bengkulu consumers as the object of research. Data collection techniques used are observation, interviews, and questionnaires. While the data analysis technique uses descriptive analysis, inferential analysis using SPSS and analysis of the coefficient of determination (R2). The results of this study indicate that Customer Relationship Management has a positive effect on Customer Satisfaction at Matahari Kota Bengkulu. This means that the more optimal the Customer Relationship Management strategy is implemented, the higher the level of customer satisfaction felt by consumers. Customer Experience has a positive effect on Customer Satisfaction for Matahari Kota Bengkulu consumers. The higher the quality of customer experience felt by consumers, the higher the level of customer satisfaction. Customer Relationship Management and Customer Experience simultaneously or together have a positive and significant effect on Customer Satisfaction at Matahari Kota Bengkulu. This is if the level of customer relationship management and customer experience is high, it will increase Customer Satisfaction in the company. Keywords : customer relationship management, customer experience, customer satisfaction